Information system for quality assurance of education - Baranenko, R.; Tyshсhenko, D.; Franchuk, T.; Sokol, H. (Полтавський національний технічний університет ім. Юрія Кондратюка, 2023)
The article analyzes the problem of developing and implementing an information system for quality assurance of higher education. The purpose of the article is to research modern methodological, technical and software tools used in the process of developing and implementing an information system for quality assurance of higher education. The peculiarities of the development of the announced information system were analyzed, on the basis of which the requirements for the design of the information system were determined, the possibilities of modification and development of the information system for ensuring the quality of education were investigated, and ways of its improvement were proposed.

У статті проаналізовано проблему розробки та впровадження інформаційної системи забезпечення якості вищої освіти. Метою статті є дослідження сучасних методичних, технічних та програмних засобів, що використовують у процесі розробки та впровадження інформаційної системи забезпечення якості вищої освіти. Проаналізовано особливості розробки анонсованої інформаційної системи, на основі яких визначено вимоги до проектування інформаційної системи, досліджено можливості модифікації та розвитку інформаційної системи забезпечення якості освіти та запропоновано шляхи її вдосконалення.
Інформаційна система забезпечення якості освіти
Keywords: management information system; information system; education; software; інформаційна система управління; інформаційні технології; освіта; програмне забезпечення